O’ZBEK TILIDA MUROJAATNING KOMUNIKATIV PRAGMATIK SHAKLLARI - Ernazarova Iroda Shavkat qizi,; To’rayeva Maftuna Abdiraim qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article analyzes the communicative-pragmatic forms of address in the Uzbek language. Formal, informal, emotional and etiquette forms of address are shown  on  the  basis  of  examples,  and  their  socio-cultural  and  speech  functions  are indicated.